GEL ANTI JERAWAT EKSTRAK DAUN BUTA-BUTA (Excoecaria agallocha L.) DAN PENGUJIAN ANTIBAKTERI Staphylococcus epidermidis - Ika Olivia Borman; Yusriadi Yusriadi; Evi Sulastri (Universitas Tadulako, 2015)
Buta-Buta (Excoecaria agallocha L.) leaf is a type of mangrove plants that has antibacterial activity againtsbacteriacausing acne, Staphylococcus epidermidis,. This study aims to formulate buta-buta leaf extract with the concentration of 12.5 % into anti-acne gel using two gels, namely HPMC 8% (Formula 1) and Carbopol 940 2%(Formula 2). Antibacterial activity test was carried out by agar diffusion method using well. The stability and antibacterial activity data during 28 days were analyzed statistically using unpaired t-student with a degree of confidence of 95% (α = 0.05). The evaluation results of anti-acne gel form of buta-buta leaf extract in Formula 2 showedbetter characteristics than Formula 1, which include organoleptic examination, homogenity, pH and viscosity during 28 days. The antibacterial test showed the diameter of inhibition zone of Formula 2 is 11.03 mm ±0,01. The statistic analysis showed a significant difference between Formula 2 with a positive control (klindamisin gel).